Sequence variants of estrogen receptor beta and risk of prostate cancer in the National Cancer Institute Breast and Prostate Cancer Cohort Consortium. - Chen, Y; Kraft, P; Bretsky, P; Ketkar, S; Hunter, D; Albanes, D; Altshuler, D; Andriole, G; Berg, C; Boeing, H; Burtt, N; Bueno-de-Mesquita, B; et al. (2007)
BACKGROUND: Estrogen receptor beta (ESR2) may play a role in modulating prostate carcinogenesis through the regulation of genes related to cell proliferation and apoptosis. METHODS: We conducted nested case-control studies in the Breast and Prostate Cancer Cohort Consortium (BPC3) that pooled 8,323 prostate cancer cases and 9,412 controls from seven cohorts. Whites were the predominant ethnic group. We characterized genetic variation in ESR2 by resequencing exons in 190 breast and prostate cancer cases and genotyping a dense set of single nucleotide polymorphisms (SNP) spanning the locus in a multiethnic panel of 349 cancer-free subjects. We selected four haplotype-tagging SNPs (htSNP) to capture common ESR2 variation in Whites; these htSNPs were then genotyped in all cohorts. Conditional logistic regression models were used to assess the association between sequence variants of ESR2 and the risk of prostate cancer. We also investigated the effect modification by age, body mass index, and family history, as well as the association between sequence variants of ESR2 and advanced-stage (>or=T3b, N1, or M1) and high-grade (Gleason sum >or=8) prostate cancer, respectively. RESULTS: The four tag SNPs in ESR2 were not significantly associated with prostate cancer risk, individually. The global test for the influence of any haplotype on the risk of prostate cancer was not significant (P = 0.31). However, we observed that men carrying two copies of one of the variant haplotypes (TACC) had a 1.46-fold increased risk of prostate cancer (99% confidence interval, 1.06-2.01) compared with men carrying zero copies of this variant haplotype. No SNPs or haplotypes were associated with advanced stage or high grade of prostate cancer. CONCLUSION: In our analysis focused on genetic variation common in Whites, we observed little evidence for any substantial association of inherited variation in ESR2 with risk of prostate cancer. A nominally significant (P < 0.01) association between the TACC haplotype and prostate cancer risk under the recessive model could be a chance finding and, in any event, would seem to contribute only slightly to the overall burden of prostate cancer.